A STUDY ON CUSTOMERS ATTITUDE TOWARDS ONLINE TICKET BOOKING DURING COVID-19 WITH SPECIAL REFERENCE TO COIMBATORE CITY (Journal of Pharmaceutical Negative Results, 2022)
An online booking system works all the time. This gives freedom to potential visitors to book a room, ticket at anytime they want. It also maximises your sales because you are not limited to your working hours. An online booking system is a piece of a software used for reservation management. In fact, studies shows that a 24/7 online reservation system greatly increases the number of bookings. With the development in science and technology the usage of online ticket booking has been increased tremendously. Increase in online literacy encourages online ticket booking and customer buying behaviour. Highly demanded lifestyle, convenience, information wide, scarcity of time induces the customers to move from traditional ticket booking to online ticket booking. During Covid the need for online ticket booking increased among the general public since people were not ready to face the crowd and they were insisted about safety. That too during pandemic people were not ready to lose their safety and they were very much conscious about their hygiene. Hence the researchers made an attempt to study on customer attitude towards online ticket booking during COVID-19 with special reference to Coimbatore city. It was found that customer preferred online ticket booking for their convenience and they are satisfied with the online ticket booking in various factors.